2020
DOI: 10.1177/1753466620954366
|View full text |Cite
|
Sign up to set email alerts
|

The use of nebulized pharmacotherapies during the COVID-19 pandemic

Abstract: Coronavirus disease 2019 (COVID-19), caused by the highly contagious novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has resulted in a worldwide pandemic and currently represents a major public health issue. COVID-19 has highlighted the need for clear and accurate guidance on the use of aerosol-generating procedures, such as nebulization, for the treatment of patients with respiratory diseases with or without COVID-19. Despite the lack of evidence, there is heightened concern about the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
0
27
0
1
Order By: Relevance
“…49,50 Given this uncertainty, many hospitals and clinics treat nebulizer therapy as an aerosol generating procedure to protect healthcare providers from SARS-CoV-2 infection. 51 Pulmonary function testing and spirometry are not currently classified as aerosol generating procedures by the CDC, 49 though the American Thoracic Society and the American Academy of Asthma, Allergy, and Immunology recognize that pulmonary function testing has the potential to generate aerosols. [4][5][6][52][53][54] A small study of five adults undergoing pulmonary function testing demonstrated aerosol generation with tidal breathing, the forced vital capacity maneuver, and maximum voluntary ventilation, though additional studies are needed.…”
Section: Principles Of Aerosol Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…49,50 Given this uncertainty, many hospitals and clinics treat nebulizer therapy as an aerosol generating procedure to protect healthcare providers from SARS-CoV-2 infection. 51 Pulmonary function testing and spirometry are not currently classified as aerosol generating procedures by the CDC, 49 though the American Thoracic Society and the American Academy of Asthma, Allergy, and Immunology recognize that pulmonary function testing has the potential to generate aerosols. [4][5][6][52][53][54] A small study of five adults undergoing pulmonary function testing demonstrated aerosol generation with tidal breathing, the forced vital capacity maneuver, and maximum voluntary ventilation, though additional studies are needed.…”
Section: Principles Of Aerosol Sciencementioning
confidence: 99%
“…Nebulized therapies are classified as a “possible aerosol generating procedure” by the CDC based on conflicting data from the SARS‐CoV epidemic 49,50 . Given this uncertainty, many hospitals and clinics treat nebulizer therapy as an aerosol generating procedure to protect healthcare providers from SARS‐CoV‐2 infection 51 . Pulmonary function testing and spirometry are not currently classified as aerosol generating procedures by the CDC, 49 though the American Thoracic Society and the American Academy of Asthma, Allergy, and Immunology recognize that pulmonary function testing has the potential to generate aerosols 4–6,52–54 .…”
Section: Transmission Of Sars‐cov‐2 Via Respiratory Droplets and Aeromentioning
confidence: 99%
“…Nebulization may increase dispersion of patient‐emitted aerosols and usage within healthcare settings has declined due to concern for transmission of SARS‐CoV‐2 to healthcare workers 9 . Nonetheless, the degree of risk remains uncertain 10,11 …”
Section: Copd and Covid‐19 Infectionmentioning
confidence: 99%
“…Withholding nebulization therapy may also lead to respiratory failure in severe cases (34). There are concerns regarding the overabundance of caution that HCPs and health institutions might exercise in their approach to the use of nebulizers that may lead to unfavourable patient outcomes (35). Hence, there is a need to shift the focus to risk-benefit assessment when it comes to the use of nebulizers in pediatric asthma management.…”
Section: Duplicate Articles N=2mentioning
confidence: 99%